2009
DOI: 10.1111/j.1365-2850.2009.01399.x
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, negative attitudes and discrimination towards mental illness within the nursing profession: a review of the literature

Abstract: The aim of this paper was to review the existing literature pertaining to stigma, negative attitudes and discrimination towards mental illness, specifically as viewed through the lens of the nursing profession. The results of the literature review were synthesized and analysed, and the major themes drawn from this were found to correspond with Schulze's model identifying three positions that healthcare workers may assume in relation to stigma of mental illness: 'stigmatizers', 'stigmatized' and 'de-stigmatizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
258
1
16

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(299 citation statements)
references
References 35 publications
16
258
1
16
Order By: Relevance
“…A recent review of the general nursing literature 25 showed that nurses held hostile attitudes toward people who had self-harmed, often viewing them as squandering precious health care resources intended to save lives. Emergency department nurses and those in intensive care units were among the most hostile toward self-harming patients and were often openly unsympathetic and demeaning.…”
Section: Stigmatization By Health Providersmentioning
confidence: 99%
“…A recent review of the general nursing literature 25 showed that nurses held hostile attitudes toward people who had self-harmed, often viewing them as squandering precious health care resources intended to save lives. Emergency department nurses and those in intensive care units were among the most hostile toward self-harming patients and were often openly unsympathetic and demeaning.…”
Section: Stigmatization By Health Providersmentioning
confidence: 99%
“…Individuals are often blamed for their selfharmful behavior, with their acts often interpreted in a limited and stigmatized manner, frequently as "attention-seeking" and "manipulative" in nature (Long, Manktelow, & Tracey, 2013;McCann, Clark, McConnachie, & Harvey, 2007;Ross & Goldner, 2009). Self-harm can evoke strong emotional reactions, with disclosures eliciting responses of confusion, frustration, anger, fear, anxiety, discomfort, and even disgust (Heath, Toste, Sornberger, & Wagner, 2011;Long et al, 2013;Marzano, Adler, & Ciclitira, 2015).…”
Section: Public Attitudes and Helpingmentioning
confidence: 99%
“…This tool consisted of 17 items with 5 point likert scale (originally the tool had 7 point likert scale) with three domains namely; Consumer capacity (8 items), Consumer involvement (5 items) and Consumer as staff (4 items). Respondents were given the choice of five response categories to tick based on their feelings from disagree strongly (1) to agree strongly (5). In this study, "Mental health consumer" or "consumer" is defined as a person who is currently using mental health services as either an in-patient or out-patient.…”
Section: Methodsmentioning
confidence: 99%
“…4 However, health professionals' attitudes have been identified as a barrier to inclusion of consumers into mental health services. 5 Research suggests that there is a need to change the mental health professionals' attitudes in encouraging clients to participate actively in planning, development, delivery and evaluation of mental health services. 6,7 On the other hand, emerging evidence suggests that mental health education influences positively on attitudes of nursing 8,9 and medical 10 undergraduates towards persons with mental illness.…”
Section: Introductionmentioning
confidence: 99%